Pemberdayaan UMKM Nuhayrun melalui Pengembangan Budidaya Lebah Tanpa Sengat menjadi Agroeduwisata Berbasis Islami - Ratni, Eli; Lendrawati; Idris, M; Mansur, Arif Rohman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Nuhayrun MSME in Nagari is a community-based enterprise that originated from the activities of the Taman Pendidikan Al-Qur’an (TPA) in Korong Patalangan, Padang Pariaman Regency. To enhance income and economic self-reliance among local residents, the enterprise has expanded its stingless bee (Galo-galo) farming into an agro-edutourism model. This community service program aims to increase the income of Nuhayrun MSME through improved production and optimized business management. The implemented methods include the addition of Heterotrigona itama and Trigona laeviceps colonies, cultivation of nectar-rich forage plants such as Calliandra and Clitoria ternatea, development of edutourism packages, human resource training, and optimization of digital promotional media. The results of the program indicate enhanced managerial awareness among partners, an increase in productive bee colonies, and the development of educational materials and promotional content that support the enterprise's image as an Islamic-based agro-edutourism center.